Flower-like cobalt carbide for efficient carbon dioxide conversion. Issue 57 (17th March 2020) - Guo, Qing; Xia, Shu-Guang; Li, Xu-Bing; Wang, Yang; Liang, Fei; Lin, Zhe-Shuai; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : Flower-like Co2 C enables photothermal catalytic CO2 –epoxide cycloaddition with yields of up to ∼95% under solar light. Abstract : Catalytic conversion of carbon dioxide (CO2 ) to value-added chemicals under mild conditions is highly desired, albeit with significant challenges. Here, in terms of exposure of abundant active sites and excellent photo-to-thermal conversion properties, flower-like Co2 C has been firstly used for effectively catalysing the cycloaddition of CO2 with epoxides to produce cyclic carbonates with yields of up to 95% under solar light. Density functional theory (DFT) calculations reveal that Lewis acid sites of the surface Co atoms can activate both CO2 and epoxide, thus opening up the possibility of a CO2 -epoxide cycloaddition reaction.